Are LeDoux's survival circuits basic emotions under a different name?. (December 2018) - Scarantino, Andrea
Abstract : In his early work, LeDoux distinguished between implicit emotions (defined as motive states) and explicit emotions (defined as states of consciousness). He has recently suggested that emotion terms like "anger" and "fear" should only be taken to refer to feelings, and that motive states are better captured by a new theory of survival circuits. In this commentary, I reject this proposal, and articulate a New Basic Emotion Theory (BET) which suggests that emotion terms should only be taken to refer to motive states, which may or may not involve feelings. Despite these differences, I will argue that there are significant similarities between LeDoux's theory of survival circuits and my own New BET.